Bone Marrow Mesenchymal Stem Cell-Derived Exosomes Modulate Chemoradiotherapy Response in Cervical Cancer Spheroids - Kesara Nittayaboon; Piyatida Molika; Rassanee Bissanum; Kittinun Leetanaporn; Nipha Chumsuwan; Raphatphorn Navakanitworakul (Pharmaceuticals)
Background: Bone marrow mesenchymal stem cells (BM-MSCs) are significant in chemo- and radiotherapy resistance. Previous research has focused on BM-MSCs, demonstrating their functional involvement in cancer progression as mediators in the tumor microenvironment. They play multiple roles in tumorigenesis, angiogenesis, and metastasis. BM-MSC-derived exosomes (BM-MSCs-exo) are small vesicles, typically 50–300 nm in diameter, isolated from BM-MSCs. Some studies have demonstrated the tumor-suppressive effects of BM-MSCs-exo. Objective: This study aimed to investigate their role in modulating the impact of chemoradiotherapy (CRT) in different types of cervical cancer spheroid cells. Methods: The spheroids after treatment were subject to size measurement, cell viability, and caspase activity. Then, the molecular mechanism was elucidated by Western blot analysis. Results: We observed a reduction in spheroid size and an increase in cell death in HeLa spheroids, while no significant changes in size or cell viability were found in SiHa spheroids. At the molecular level, CRT treatment combined with BM-MSCs-exo in HeLa spheroids induced apoptosis through the activation of the NF-κB pathway, specifically via the NF-κB1 (P50) transcription factor, leading to the upregulation of apoptosis-related molecules. In contrast, CRT combined with BM-MSCs-exo in SiHa spheroids exhibited an opposing effect: although cellular viability decreased, caspase activity also decreased, which correlated with increased HSP27 expression and the subsequent downregulation of apoptotic molecules. Conclusion: Our study provides deeper insight into the potential of BM-MSCs-exo in cervical cancer treatment, supporting the development of more effective and safer therapeutic strategies for clinical application.